Digital literacy in Turkish high school science textbooks - ÇAKIR, MUSTAFA (My University, 2023)
In the 21st century, many innovations have been reflected in the educational sector and changed teaching and learning practices. Changes in the process of acquiring and using knowledge, differentiating student characteristics, innovations in accessing digital resources, and changing understandings of what to learn and how to learn required rethinking traditional methods and reforming education. One of the skills that entered the curriculum and textbooks with the education reforms is digital literacy. In this context, it is necessary to examine science textbooks in terms of digital literacy. The aim of this study is to examine the high school science textbooks approved and distributed by the Turkish Ministry of National Education in terms of digital literacy. Within the scope of the study, a textbook evaluation rubric was developed based on the UNESCO Digital Literacy Competence Framework. The study was carried out with a qualitative research approach and document analysis was used as a research design. Research data were analyzed by the comparative descriptive analysis method. The references to digital competence areas in textbooks increase with the increase in grade level. In the books examined, the area of competence that takes place at the highest rate at all grade levels is "information and data literacy". There is no content in the textbooks within the scope of "careerrelated competencies". The level of including "security" and “problem-solving" competencies in the reviewed books is quite low. It can be expected that references to "problem-solving" competencies would be higher in high school science textbooks since high school students are expected to have required higher-order thinking skills and required cognitive abilities. Additionally, it is very important to provide the new generation of students, who are digital natives, with security-related competencies such as understanding the risks and threats in the digital environment and protecting personal data and privacy